The Role of Perception in Personality Development - Rustam qizi, Do`sjanova Nilufar (Journal of Ethics and Diversity in International Communication, 2023)
the article talks about the current interpretation of perception, its different recognition from the side of scientists, its features, its specific facets today, its classification, forms, and the processes associated with perception in medicine.